2008
DOI: 10.1007/s11746-008-1310-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Addition of Waxes on the Crystallization Behavior of Anhydrous Milk Fat

Abstract: Physicochemical characteristics of lipid-based foods depend, among other factors, on the microstructure and the characteristics of the lipid network formed during crystallization. The objective of this study, was to evaluate the effect of the addition of sunflower oil waxes on the crystallization and melting behavior of anhydrous milk fat (AMF), a lipid with a low content of palmitic and transfatty acids. The crystallization and melting behavior of AMF alone and with the addition of 0.25 and 0.5% of waxes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
35
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 25 publications
12
35
0
1
Order By: Relevance
“…However, in the presence of 3% CW, the onset for TP crystallization occurred at a higher temperature (i.e., 13.3°C) than in the systems without CW, a process associated with the heterogeneous nucleation of TP. Similar results have been previously observed in a system formed by anhydrous milk fat and sunflower wax 28 , and in the same CW-TP system at a cooling rate of 10°C/min. 12 Thus, the higher SFC and higher temperature for TP crystallization observed in the CW-TP organogels ( Table 1) was associated with the presence of TP and its heterogeneous nucleation induced by the initial crystallization of CW.…”
Section: Resultssupporting
confidence: 89%
“…However, in the presence of 3% CW, the onset for TP crystallization occurred at a higher temperature (i.e., 13.3°C) than in the systems without CW, a process associated with the heterogeneous nucleation of TP. Similar results have been previously observed in a system formed by anhydrous milk fat and sunflower wax 28 , and in the same CW-TP system at a cooling rate of 10°C/min. 12 Thus, the higher SFC and higher temperature for TP crystallization observed in the CW-TP organogels ( Table 1) was associated with the presence of TP and its heterogeneous nucleation induced by the initial crystallization of CW.…”
Section: Resultssupporting
confidence: 89%
“…This phenomenon was associated with the heterogenous nucleation of TP induced by the initial crystallization of CW. These results are in line with the ones obtained by Martini et al, 3 who observed that, under isothermal conditions, the induction time of crystallization of anhydrous milk fat decreased as the Fig. 4 Melting parameters as a function of CW concentration for organogels developed at the T set 's indicated with 0% TP (a, c, and e), with 0.5% or with 1.0% TP (b, d, and f).…”
Section: Thermal Behavior Of Cw-tp Solutions In Hosfosupporting
confidence: 90%
“…The results and the ones obtained by Martini et al 3 showed that the triacylglycerides-wax (i.e., sunflower oil wax, CW, and carnauba wax) interaction during crystallization might be a useful alternative to tailor particular physicochemical properties associated to a specific functionality (i.e., melting profile and texture). Organogelation of vegetable oil might be used to develop trans-free vegetableoil-based spreads and coatings and also novel food products with distinctive textural perceptions for the consumers.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations